IMPLEMENTATION OF THE FAMILY PLANNING VILLAGE (KB) PROGRAM IN CONTROLLING THE BIRTH RATE IN LIPUKASI VILLAGE, TANETE RILAU DISTRICT, BARRU REGENCY - Karyawati, Seni; Guntur, Muhammad; Yamin, Muh Nur; Johansyah, Oky Nur Pratiwi (Universitas Negeri Makassar, 2025)
This research aims to determine the implementation of the Family Planning Village (KB) Program in Controlling the Birth Rate in Lipukasi Village, Tanete Rilau District, Barru Regency. This type of research is qualitative with data collection techniques carried out by means of observation, interviews, and documentation. The data analysis technique used consisted of data reduction, data presentation and drawing conclusions. The research results show that the Family Planning Program is quite effective in controlling the birth rate in Lipukasi Village. This can be seen from the results of interviews which show that the implementation of government programs has been going quite well. As well as PUS' understanding and knowledge of the family planning program also showed good results. And seen from the policy implementation indicators, namely: Interests influenced by the policy, Type of benefits generated, Degree of change desired, Location of decision making, program implementers, Resources deployed, Power, interests and strategies of the actors involved, Characteristics of institutions and authorities, Compliance and responsiveness. However, there are still several obstacles faced in implementing the Family Planning Program, namely that there are still people who do not understand or do not participate in the Family Planning Program for various reasons.